Purification of Polysaccharide Produced by the Haploid Yeast Strain of Tremella sanguinea and Its Antioxidant and Prebiotic Activities - Liu, Yichi; Chen, Suo; Zhang, Jialan; Gao, Mengxiang; Li, Li (Molecules (Basel, Switzerland), 2023)
Tremella sanguinea is a traditional Chinese medicinal and edible mushroom. Polysaccharides from Tremella mushrooms have received increasing amounts of research attention due to their diverse pharmacological activities. In this study, via the incubation of basidiospores collected from fresh artificially cultivated basidiocarps of T. sanguinea, a haploid yeast strain of T. sanguinea was obtained, and it was found to be a typical loose-slime-forming yeast capable of producing a large amount of exopolysaccharides (EPS). Using DEAE-52 cellulose column chromatography and Sephadex G-100 gel permeation chromatography, the major polysaccharide, named TSPS-1, was separated and purified from the EPS produced by the haploid yeast strain of T. sanguinea. TSPS-1 was a homogeneous polysaccharide with a molecular weight of 2.5 × 103 kDa and consisted of rhamnose, glucose, xylose, mannose and glucuronic acid at a molar ratio of 1: 0.7: 62.2: 24.6: 11.5. The bioactivity of the TSPS-1 polysaccharide was evaluated. The results show that TSPS-1 exhibited noticeable antioxidant activity by scavenging hydroxyl radicals (EC50 = 1.92 mg/mL) and superoxide radicals (EC50 = 1.33 mg/mL), and prebiotic activity by promoting the growth of different probiotic strains in the genus Lactobacillus and Bifidobacterium. These results suggest that the cultivation of the haploid yeast strain can be a promising alternative for the efficient production of valuable T. sanguinea polysaccharides with antioxidant and prebiotic potential.